Community-Centered Security and Human Rights: The Role of Civil-Military Cooperation in Nigeria’s Counter-Terrorism Strategy - Imokhai, Philip Ikhanafe; Momoh, Ibrahim (NIU Journal of Social Sciences; Vol 11 No 4 (2025): NIU Journal of Social Sciences, Vol. 11 No. 4, December 2025, 2025)
Nigeria’s counter-terrorism strategy, particularly in the Northeast, has been marked by an overreliance on military force, which while weakening Boko Haram and ISWAP, has simultaneously deepened distrust between security forces and local communities due to recurring reports of human rights violations. This study interrogates the prospects of a community-centered security model that foregrounds civil-military cooperation (CIMIC) as a means of reconciling state sovereignty with humanitarian imperatives. Anchored in Human Security Theory, Social Contract Theory, and Institutional Theory, among others, the paper situates Nigeria’s counter-terrorism challenge within broader debates on people-centered security and legitimacy. Drawing on case studies from Borno, Adamawa, and Yobe States, alongside comparative lessons from Kenya and Niger, the research examines how participatory approaches such as community-led intelligence gathering, inclusive policing, and post-conflict reintegration can enhance operational effectiveness while reducing abuses. The findings highlight that where trust-building mechanisms and civil-military dialogue have been institutionalized, communities have provided more reliable intelligence and shown greater willingness to cooperate with state forces. However, structural weaknesses, poor accountability, and entrenched militarization continue to limit outcomes. The paper contributes to methodological literature in political science and development studies by proposing a framework for participatory counter-terrorism in fragile states. Policy recommendations emphasize rights-based engagement, institutional reform, and multi-stakeholder collaboration as prerequisites for sustainable peace and security in Nigeria. Keywords:  Counter-terrorism, Civil-Military Cooperation (CIMIC), Insurgency, Human Security.